2017
DOI: 10.2139/ssrn.2982617
|View full text |Cite
|
Sign up to set email alerts
|

The Agency Problems of Institutional Investors

Abstract: We analyze how the rise of institutional investors has transformed the governance landscape. While corporate ownership is now concentrated in the hands of institutional investors that can exercise stewardship of those corporations that would be impossible for dispersed shareholders, the investment managers of these institutional investors have agency problems vis-à-vis their own investors. We develop an analytical framework for examining these agency problems and apply it to study several key types of investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 24 publications
(11 reference statements)
3
69
0
1
Order By: Relevance
“…Their model thus shows agency conflicts between shareholders and managers do not necessarily weaken the predictions of the above theories. Instead, agency conflicts that may reduce incentives especially of passively diversified investors to engage in governance (Bebchuk et al 2017) can be the vehicle by which CoOCo reduces investment and output, and at the same time increases industry profits. Because shareholders design incentive contracts the manager takes as given, their model also clarifies that managers need not be aware of their and competitor firms' ownership structures for common ownership to affect corporate behavior.…”
Section: Alternative Objectives Of the Firm Managerial Incentives Amentioning
confidence: 99%
See 1 more Smart Citation
“…Their model thus shows agency conflicts between shareholders and managers do not necessarily weaken the predictions of the above theories. Instead, agency conflicts that may reduce incentives especially of passively diversified investors to engage in governance (Bebchuk et al 2017) can be the vehicle by which CoOCo reduces investment and output, and at the same time increases industry profits. Because shareholders design incentive contracts the manager takes as given, their model also clarifies that managers need not be aware of their and competitor firms' ownership structures for common ownership to affect corporate behavior.…”
Section: Alternative Objectives Of the Firm Managerial Incentives Amentioning
confidence: 99%
“…Relatedly, some have argued that passive funds' competitive pressures imply their primary objective is cost reduction, leading to reduced incentives to engage to increase the value of the firms they beneficially own on behalf of their investors, see an informal discussion in Bebchuk et al (2017). The premise of this argument is disputed and appears to conflict with empirical facts, as discussed below.…”
Section: Governance Channelsmentioning
confidence: 99%
“…307 The largest five shareholders (mostly mutuals) owned an average 20.8% in the top-twenty corporations. 308 It has been found that mutual firms have already caused rising consumer prices. 309 This has been described as "the major new antitrust challenge of our time."…”
Section: Figurementioning
confidence: 99%
“…shares. Moreover, active managers face somewhat stronger voting incentives than those of passive managers (Kahan and Rock, 2007;Shapiro-Lund, 2017;Bebchuk, Cohen, and Hirst, 2017). An active manager can improve their portfolio's return relative to competitors by taking actions that increase the value of a stock in which the manager is overweight relative to the market.…”
Section: The Determinants Of Mutual Fund Voting Behaviormentioning
confidence: 99%